2013
DOI: 10.1080/02699931.2012.698251
|View full text |Cite
|
Sign up to set email alerts
|

Positive feelings facilitate working memory and complex decision making among older adults

Abstract: The impact of induced mild positive feelings on working memory and complex decision making among older adults (aged 63-85) was examined. Participants completed a computer administered card task in which participants could win money if they chose from "gain" decks and lose money if they chose from "loss" decks. Individuals in the positive-feeling condition chose better than neutral-feeling participants and earned more money overall. Participants in the positive-feeling condition also demonstrated improved worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 23 publications
2
42
4
Order By: Relevance
“…Consistent with this theory, positive affect is associated with reduced morbidity for a variety of known risk factors (e.g. cardiovascular; chronic stress) for AD (Boehm and Kubzansky, 2012; Pressman and Cohen, 2005; Steptoe et al , 2005), enhanced cognitive functioning (Ashby et al , 1999; Carpenter et al , 2013; Yang et al , 2013), and as our work suggests, relatively higher levels of cerebral glucose metabolism in regions vulnerable to early neuropathological changes. Thus, interventions targeting positive affect could have potential in mitigating pathological processes associated with cognitive and functional decline through increasing flexible and adaptive responses (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with this theory, positive affect is associated with reduced morbidity for a variety of known risk factors (e.g. cardiovascular; chronic stress) for AD (Boehm and Kubzansky, 2012; Pressman and Cohen, 2005; Steptoe et al , 2005), enhanced cognitive functioning (Ashby et al , 1999; Carpenter et al , 2013; Yang et al , 2013), and as our work suggests, relatively higher levels of cerebral glucose metabolism in regions vulnerable to early neuropathological changes. Thus, interventions targeting positive affect could have potential in mitigating pathological processes associated with cognitive and functional decline through increasing flexible and adaptive responses (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, “Interesting” held the most responses in the Positive category. A growing body of literature [15,37,38] now suggests that positive affect can improve individuals' information processing and the quality of their health decision making. Interventions aimed at capturing positive affect and engagement associated with the receipt of PGT could enhance the processing of health information incorporated into interventions and produce greater behavior change and salience.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, previous research with reinforcement learning has shown that faster reaction times are associated with greater striatal dopamine efficacy (Caldú et al, 2007; Frank et al, 2007b; Niv et al, 2007; Frank et al, 2009), suggesting that this is a dopaminergic effect. Subjective pleasure can have considerable influences on cognitive performance such that even slight mood changes can alter reinforcement learning, and this effect is thought to rely on enhanced dopamine transmission (Carpenter et al, 2013; for a review see Ashby et al, 1999). Consistent with this, we found that higher subjective pleasantness ratings of the neutral music corresponded to faster reaction times (Figures 8B, 9B), demonstrating that even within the neutral musical condition, responses accelerated when subjects enjoyed the music more.…”
Section: Discussionmentioning
confidence: 99%